(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This study aimed to isolate Aliarcobacter cryaerophilus in ready-to-cook poultry meat in Bangladesh. Materials and Methods: Thirty drumstick samples were collected from super shops in Dhaka city (n = 10), Mymensingh city (n = 10), and Patuakhali town (n = 10). After sample processing, they were cultured in Blood agar media with Campylobacter base using a microfilter (0.42 nm). Suspected colonies were subjected to DNA extraction and PCR assay targeting 16SrRNA genes. Then, sequencing was performed for confirmation. Results: Of 30 samples, 3 (10%) were positive for A. cryaerophilus. Phylogenetic analysis shows that our isolate has strong similarities with one of the isolates from China. Conclusion: The presence of this organism in ready-to-cook poultry meat is a significant concern for consumers as it bears zoonotic importance. J. Adv. Vet. Anim. Res., 10(1): 113–117, March 2023 http://doi.org/10.5455/javar.2023.j659